Liberia Public Expenditure Review : Options for Fiscal Space Enlargement - World Bank (Washington, DC, 2014)
Liberia's post-conflict reconstruction and rehabilitation has been successful. Peace, stability and security gradually returned and provided an enabling environment for the rebuilding of this war-torn country. Over the next five years (2013-2017), the Bank will focus on building infrastructure (energy and transport), increasing youth employment opportunities, strengthening human development and sustaining peace and security. This note considers how to increase Liberia s fiscal space by examining four options: 1) improving the efficiency of public expenditure, 2) increasing external grants, 3) increasing domestic revenue, and 4) increasing borrowing (domestic and/or external). While any increase in fiscal space gained from the first two options will not impose a burden in terms of debt or tax on the economy, the latter two will impose such burdens. In its examination of public expenditure by economic classification, this note finds that fiscal space in Liberia can be created by further improving the technical efficiency of current expenditure (wages and salaries, goods and services and transfers to state owned enterprises). However, the size of the fiscal space gained from these measures is difficult to pinpoint.